A supply chain management quality management and competitive advantage framework for Thai orchid exporters - Pungam, K.; Atthirawong, W. (My University, 2019)
This study aims to develop a conceptual framework of supply chain management (SCM), quality management (QM), and competitive advantage (CA) for agricultural business, specifically, the Thai orchid industry. Papers relating to elements of SCM, QM, and CA adopted by different organisations in the small-to-medium size enterprises (SMEs) sector were reviewed. The conceptual framework comprises three elements: first, SCM, which includes strategic supplier partnerships, customer relationships, and information sharing; second, quality management, which includes top management commitment, customer focus, employee involvement, and continuous improvement, and finally, competitive advantage, including price and cost-based, product-based, and service-based advantages. The literature review reveals SCM and QM have the strongest influence on CA. Thus, we propose conceptual frameworks of the relationship between SCM, QM, and CA. After developing the conceptual framework, we aim to create questionnaire as a research instrument. This will be sent to Thai orchid exporters and the responses will be analysed using the structural equation modelling (SEM) approach.
Keywords: Competitive advantage; Quality management; Supply chain management